Pengaruh Transisi Kurikulum 2013 ke Kurikulum Merdeka Belajar dan Proyek P5 Terhadap Pelaksanaan Pembelajaran (Studi di Sman 1 Pakel) - Nailariza - Umami; Mayke Zelin Deviola Rista (Jurnal Pendidikan Ekonomi, 2023)
This study discusses the influence of the 2013 Curriculum Transition to the Independent Learning Curriculum and the P5 Project on Learning Implementation. This study is motivated by educational problems so far the learning is only group discussions and then it is required to think critically, ask questions and end with presentations, but in the independent learning curriculum this is interspersed with projects to strengthen the profile of Pancasila students so that it creates a distinct impression, besides that in the 2013 curriculum there is specialization in the science majors in high school, in the independent learning curriculum nothing is replaced by selecting subjects according to the interests and talents of students in the implementation of learning. It is the differences in the 2013 curriculum and the independent learning curriculum that make researchers interested in researching. This study aims to determine whether or not there is an effect of the 2013 Curriculum Transition to the Free Learning Curriculum and the P5 Project Towards Learning Implementation. This research is a quantitative study using the Proportionate Stratified Random Sampling technique and the data collection method uses a questionnaire. The research subjects were 90 class X students of Sman 1 Pakel. The data analysis technique using multiple linear regression obtained the results of tcount (0.472) < ttable(1.987.) and tcount (9.325) > ttable (1.987). Simultaneously obtained Fcount (72.355)> Ftable (3.10). Thus in this study it was stated that there was no influence between the 2013 Curriculum Transition to the Independent Learning Curriculum on the implementation of learning but there was an influence between the P5 Project on the implementation of learning